Alcohol expectancies pre-and post-alcohol use disorder treatment: Clinical implications. (May 2018) - Coates, Jason M.; Gullo, Matthew J.; Feeney, Gerald F.X.; Young, Ross McD.; Dingle, Genevieve A.; Connor, Jason P.
Abstract: Background and aims: Modification of elevated positive expectations of alcohol consumption (alcohol outcome expectancies; AOEs) is a key feature of Cognitive Behaviour Therapy (CBT) approaches to Alcohol Use Disorders (AUDs). Despite extensive research supporting the efficacy of CBT for AUD, few studies have examined AOE change. This study aimed to assess AOE change following completion of CBT for AUD and its association with drinking behaviour. Method: One-hundred and seventy-five patients who completed a 12-week CBT program for AUD were administered the Drinking Expectancy Questionnaire (DEQ) at pre-treatment assessment and upon completion of treatment. Abstinence was achieved by 108 (61.7%) of completing patients. For patients who lapsed, the mean proportion of abstinent days was 93%. Results: DEQ scales assessing expectations of positive alcohol effects on tension reduction, assertiveness, and cognitive enhancement were significantly lower post-treatment ( p < 0.001). Expectations of negative effects on mood were higher post-treatment ( p < 0.001). The largest AOE change occurred on the tension reduction scale. Greater percentage of abstinent days over treatment was associated with lower pre-and post-treatment tension reduction expectancy scores ( p < 0.05). Drinking during treatment was associated with smaller changes in expectations of negative effects of alcohol on mood ( p < 0.05). Conclusions: Individuals who completed CBT treatment for AUD showed significant AOE change. Tension reduction and affective change expectancies may be particularly important for abstinence and useful markers of lapse risk. Highlights: Changes in alcohol outcome expectations (AOEs) among patients treated for Alcohol Use Disorder were assessed. Expectations that alcohol would positively affect assertiveness, tension reduction, and cognition were lower post-treatment. Expectations that alcohol would negatively affect mood were more strongly endorsed post treatment. Higher percentage of drinking days over treatment was associated with less change in expectation of negative effects on mood. Higher tension reduction scores were related to more drinking behaviour over the course of treatment.